Genetic dissection of tomato rootstock effects on scion traits under moderate salinity - Asins, María J.; Raga, Verónica; Roca, Dolors; Belver, Andres; Carbonell, Emilio A. (2017)
The present study approaches the QTL dissection of rootstock effects on a commercial hybrid variety grafted on a population of RILs derived from Solanum pimpinellifolium, genotyped for 4370 segregating SNPs from the SolCAP tomato panel and grown under moderate salinity. Results are compared to those previously obtained under high salinity. The most likely functional candidate genes controlling the scion [Na+] were rootstock HKT1;1 and HKT1;2 as it was previously reported for non-grafted genotypes. The higher fruit [Na+] found when rootstock genotype was homozygote for SpHKT1 supports the thesis that scion HKT1 is loading Na+ into the phloem sap in leaves and unloading it in sink organs. A significant increment of small, mostly seedless, fruits was found associated with SlHKT1 homozygous rootstocks. Just grafting increased the incidence of blossom end rot and delayed fruit maturation but there were rootstock RILs that increased commercial fruit yield under moderate salinity. The heritability and number of QTLs involved were lower and different than those found under high salinity. Four large contributing (>17 %) rootstock QTLs, controlling the leaf concentrations of B, K, Mg and Mo were detected whose 2 Mbp physical intervals contained B, K, Mg and Mo transporter-coding genes, respectively. Since a minimum of 3 QTLs (two of them coincident with leaf K and Ca QTLs) were also found governing rootstock-mediated soluble-solids content of the fruit under moderate salinity, grafting desirable crop varieties on stress-tolerant rootstocks tenders an opportunity to increase both salt tolerance and quality.